Teacher's handbook contextualized language instruction - Shrum, Judith L.; Glisan, Eileen W. (Heinle Cengage Learning, 2010)
Designed to prepare you to teach foreign language, this handbook incorporates the Standards for Foreign Language Learning in the 21st Century, and provides a practical framework for integrating the Five C's into foreign language teaching.